2020
DOI: 10.1093/crocol/otaa001
|View full text |Cite
|
Sign up to set email alerts
|

The Copper/Zinc Ratio Correlates With Markers of Disease Activity in Patients With Inflammatory Bowel Disease

Abstract: Background Zinc (Zn) and copper (Cu) are trace elements that serve as cofactors in catalytic processes with impact on immune responses. In patients with inflammatory bowel disease (IBD), decreased levels of serum Zn and Cu have been observed. Here, we investigated the effect of inflammation on serum concentrations of these trace elements in patients with IBD. Methods In this cross-sectional study, 98 patients with Crohn disea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 43 publications
2
21
0
Order By: Relevance
“…Bui et al found that CRP was associated with serum ferritin and Cu concentrations in apparently healthy school children [54]. Schneider showed that, in patients with Crohn disease (CD) and ulcerative colitis (UC), CRP was positively correlated with serum Cu and the Cu/Zn ratio in both CD and UC [98]. Our results indicated that, in this series of children and adolescents with chronic disease, the serum Cu and Cu/Zn ratio showed a stronger and more significant association with ESR than with CRP.…”
Section: Blood Analysis and Inflammatory Responsementioning
confidence: 99%
“…Bui et al found that CRP was associated with serum ferritin and Cu concentrations in apparently healthy school children [54]. Schneider showed that, in patients with Crohn disease (CD) and ulcerative colitis (UC), CRP was positively correlated with serum Cu and the Cu/Zn ratio in both CD and UC [98]. Our results indicated that, in this series of children and adolescents with chronic disease, the serum Cu and Cu/Zn ratio showed a stronger and more significant association with ESR than with CRP.…”
Section: Blood Analysis and Inflammatory Responsementioning
confidence: 99%
“…Zinc concentrations are typically decreased from 15 to 40% in affected individuals. Conversely, copper concentrations are increased in these individuals ( Schneider et al, 2020 ). This observation is in line with many studies, including research on ASD, that show that zinc and copper interact at the mucosal level and in the blood, where the ratios are inversely related ( Li et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…Systemic inflammation has the opposite effect on serum Zn and Cu concentrations, resulting in an increased Cu-to-Zn ratio [47]. In contrast to Zn, Cu concentrations increase during the acute-phase response [48].…”
Section: Discussionmentioning
confidence: 99%